2019
DOI: 10.1002/pbc.27907
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genetic counseling and testing in the pediatric oncology setting: Parental attitudes and influencing factors

Abstract: Background: Cancer predisposition syndromes (CPS) are caused by germline pathogenic variants that put an individual at increased risk of developing cancer throughout their lifetime. It is estimated that approximately 10-15% of children with cancer have an underlying CPS. Although research has investigated the clinical utility of genetic testing for children diagnosed with cancer, this study aimed to gain a deeper understanding of parental attitudes toward genetic testing in this population. Procedure: Attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The group surveyed parents of children recently diagnosed with cancer and found that 64.3% (27/42) were familiar with genetic counseling and that 50% (21/42) were interested in pursuing genetic counseling/testing but referral was not offered to 59.5% (25/42). 63 Interest in genetic testing was not dependent on personal or family history of cancer or features suggestive of a CPS as described by Jongmans et al 11 Thus, the authors suggest that it is reasonable to consider referral to genetics for evaluation of a CPS despite family history in a pediatric oncology setting. 63 Together, these data suggest genetics specialists are being underutilized whether due to the urgency of cancer treatment planning and disease management, or lack of genetics knowledge in the referring physician.…”
Section: Family History Informationmentioning
confidence: 95%
“…The group surveyed parents of children recently diagnosed with cancer and found that 64.3% (27/42) were familiar with genetic counseling and that 50% (21/42) were interested in pursuing genetic counseling/testing but referral was not offered to 59.5% (25/42). 63 Interest in genetic testing was not dependent on personal or family history of cancer or features suggestive of a CPS as described by Jongmans et al 11 Thus, the authors suggest that it is reasonable to consider referral to genetics for evaluation of a CPS despite family history in a pediatric oncology setting. 63 Together, these data suggest genetics specialists are being underutilized whether due to the urgency of cancer treatment planning and disease management, or lack of genetics knowledge in the referring physician.…”
Section: Family History Informationmentioning
confidence: 95%
“…42 A further challenge is navigating client fears regarding genetic counselling sessions. 23,152 In Saudi Arabia, "'counselling" is not a term in general use and patients have no prior understanding of the process. When creating appointments, patients are asked an extensive panel of questions regarding their family history of cancer, which can cause distress.…”
Section: Familial Cancer Genetic Counselling Clinic In Saudi Arabiamentioning
confidence: 99%
“…50 The decision to select the correct genetic test and how the data are interpreted and communicated the patient remain ongoing issues in these areas. 22,23,41,42 An additional challenge is determining the goals of testing and the information required. Furthermore, genetic counsellors must successfully communicate risk perception to their patients.…”
Section: Familial Cancer Genetic Counselling Clinic In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genetic concepts remained unfamiliar to one-third of parents. Another survey of parents of children with cancer found that most parents reported interest in cancer genetic counseling and testing, but the majority were not offered cancer genetic counseling (Desrosiers et al, 2019). Finally, semi-structured interviews with parents and adolescents found that although families were satisfied with cancer genetic counseling, reported acceptance of genetic testing, and understood the benefit of testing their child, the sessions produced complex emotional reactions and families indicated that they struggled with retaining genetic information during this 'emotionally taxing' time (McGill et al, 2019).…”
Section: Introductionmentioning
confidence: 99%